Impact of postpartum metritis on the regeneration of endometrial glands in dairy cows - I. Sellmer Ramos; J.G.N. Moraes; M.O. Caldeira; S.E. Poock; T.E. Spencer; M.C. Lucy (JDS Communications, 2023)
The postpartum uterus involutes to its pre-pregnant and fully functional state within approximately 60 d after calving. Uterine glands are essential for fertility but little is known about their regeneration postpartum. Likewise, the effect of uterine disease (metritis) on gland regeneration is unknown. We hypothesized that uterine glands would be regenerated early postpartum and that metritis would be associated with slower gland regeneration to affect their numbers later postpartum during the breeding period. Postpartum dairy cows were diagnosed as healthy (n = 17 and 9 for experiment [Exp.] 1 and 2) or metritis (n = 17 and 10 for Exp. 1 and 2, respectively) at 7 to 10 d postpartum. Cows were slaughtered at approximately 1 mo (Exp. 1) or approximately 80 or 165 d (Exp. 2) postpartum for the collection of the uterus. Uterine tissue was sectioned and the number of glandular cross-sections per unit area was counted and cross-sectional area measured. Cellular proliferation within the luminal epithelium (LE) and glandular epithelium (GE) was quantified by MKI67 (marker of cellular proliferation) immunohistochemistry. In early postpartum cows (Exp. 1), the greatest amount of MKI67 staining was found in the deep endometrium (cells closest to the myometrium). Cows with purulent material in the uterine lumen at d 30 slaughter (Exp. 1) had fewer endometrial glands per unit area in the deep and middle endometrium when compared with nonpurulent cows. The MKI67 staining was less in the deep endometrial GE and LE for purulent compared with nonpurulent cows. Estrus cyclicity was associated with a greater number of gland cross-sections in the deep and middle endometrium. Later postpartum (80 and 165 d; Exp. 2), there was greater glandular development compared with Exp. 1 and a tendency for a lesser number of gland cross-sections per unit area in diseased cows without an effect on MKI67 staining in the GE or LE. We conclude that uterine disease slows the development of uterine glands early postpartum (by 1 mo) through a mechanism that involves cellular proliferation within the GE. The impact of the early postpartum disease on glandular development later postpartum (Exp. 2) appeared to be less. Additional time, therefore, may allow recovery of the GE in later postpartum cows.